Performance of Concrete Containing Ground Granulated Blast Furnance Slag as Cement Replacement - Abdul Chalid (LP3 UMY, 2015)
This thesis deals with on inrtestigation on the perjormance of concrete containing ground grcmulated blast-.furnace (GGBF) slag, as a parlial cement replacement. Tsets were conducted on concrele in which 0, 40, and 60 percent (by weight) ofordinary Portland cemenl, was replaced by BBGF slag. Water-cementitious (w:c) ratio of 0.4 was usedfor all mixes. Concrete moist cured at 20' C, 27" C, cured at site, ond sured in seo-\oater were tested al ages herween three days and one year.for compressive strenghL The results also showed that with increasing age, lhe compressive strenght ofconcrete increases. This is due lo the combined efect oflhe deccreose in volume ol large pores and partial pore blocking resultinglrom lhe cement replacement material